Peranan Badan Pertimbangan Jabatan dan Kepangkatan dalam Penyelenggaraan Mutasi Pegawai Negeri Sipil di Kabupaten Halmahera UtaraPeranan Badan Pertimbangan Jabatan dan Kepangkatan dalam Penyelenggaraan Mutasi Pegawai Negeri Sipil di Kabupaten Halmahera Ut - Kapita, Mutlaben; Pangkey, Masje Silija; Pombengi, Jericho Denga (Sam Ratulangi University, 2015)
Abstract: The research objective was to determine the role of the Advisory Board Position and Rank in theadministration of personnel transfers structural position as mandated by Law No. 43 of 1999 on changesto Law No. 8 of 1974 About the Fundamentals of Civil Service that in the appointment, transfer anddismissal of employees must be based principles of professionalism of employees which includecompetence, work performance, and level rank Civil Servant. To determine the role of the Advisory BoardPositions and Ranks in the implementation of personnel transfers structural position, the research methodused is qualitative method, which is where the researcher as a key instrument in the study consisted of 13informants.The role of the Advisory Board Position and Rank in the administration of personnel transfers in NorthHalmahera is his duty to give consideration and advice in terms of personnel transfers by taking intoaccount the competence, performance and level of rank is not everything is going well. Because the data isbased on mutations in January that there are many employees who are placed not in accordance with theprinciples of The riht Man On The Right Place even exist in mutation employee has concurrently. And sois the implementation of personnel transfers more attention to long term in-service tasks, proximity orkinship relationships compared with competence, work performance and level rank for employeestransferred. And there is recognition of employees that once issued Decree of the new regent he knowshimself in mutasikan on new positions.To avoid the Spoil System Advisory Board Positions and Ranks need to cooperate with an independentassessment team and has experience in assisting the selection of employees transferred. And to the resultsof the session of the Advisory Board Positions and Ranks recommended to the Regional Personnel Officerin a transparent manner for the sake of accountability in policy mutation. Similarly, to get a goodemployee performance, then it should in the implementation of personnel transfers expected considerationAgency Position and Rank refers to Law Number. 43 of 1999 on changes to Law No. 8 of 1974 About theFundamentals of Civil Service which is technically explained that the appointment or removal shall be inaccordance with the Civil Servants professionalism.Keywords: The role of the Advisory Board Position. Rank in the Implementation of Civil ServantsMutation.